Accounting Information and Excess Stock Returns: The Role of The Cost of Capital - New Evidence From US Firm-level Data - Apergis, Nicholas; Artikis, G.; Eleftheriou, S.; Sorros, J. (Routledge Taylor & Francis Group, 2012)
The goal of this article is to investigate the impact of accounting information on the cost of capital as well as how the latter influences excess returns. The analysis has certain novelties: first, it extends prior works by investigating how certain components of accounting information affect stock returns through its direct effect on the cost of capital by incorporating influential components of accounting information; second, it makes use of a sample of 330 US manufacturing firms spanning the period1990Q1 to 2009Q2, while it makes use, for the first time in this literature, of the methodology of panel cointegration. The empirical findings display that accounting information affects directly the firm’s cost of capital. This, in turn, tends to exert a negative effect on the firm’s excess stock returns, an empirical documentation not captured in case researchers attempt to directly link the cost of capital and excess stock returns.